INVERSION OF THE SELF-POTENTIAL METHOD FIXED GEOMETRY APPROACH AND ITS APPLICATION FOR ENVIRONMENTAL AND NATURAL RESOURCE STUDIES - Tigor Parluhutan Lubis, Arion
The electrical potential on the Earth's surface can be studied using methods from the field of geophysics. One such method is the self-potential method, which aims to obtain information related to natural static potential caused by subsurface anomalies. The steps in this method start with electrode construction, field data acquisition, elevation and position correction, and proceed to inverse modeling, which results in a comparison between field data and data calculated using the Levenberg-Marquardt method. The results from synthetic data have been illustrated in graphical form. The field data obtained is then processed in the order mentioned earlier. Based on the research, the distribution of electrical potential values obtained from the study area ranges from 47mV to 240.72mV. The anomaly in the study area is a vertical cylinder located at a depth of 14 meters, with a shape factor of 0.2432, an angle of 91.48°, and a dipole moment of -58.5677.